If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5y + -2) = 6y Reorder the terms: 2(-2 + 5y) = 6y (-2 * 2 + 5y * 2) = 6y (-4 + 10y) = 6y Solving -4 + 10y = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -4 + 10y + -6y = 6y + -6y Combine like terms: 10y + -6y = 4y -4 + 4y = 6y + -6y Combine like terms: 6y + -6y = 0 -4 + 4y = 0 Add '4' to each side of the equation. -4 + 4 + 4y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 4y = 0 + 4 4y = 0 + 4 Combine like terms: 0 + 4 = 4 4y = 4 Divide each side by '4'. y = 1 Simplifying y = 1
| (-6x^2)+24x+18=0 | | -5+15=13x-3-12x | | 4y+228=356 | | -16n+16=-14n-12 | | y-1=(x+3)*(x+3) | | 4p+9+(-7p+2)= | | -17-22y= | | -7m=-49 | | x(-9)=27 | | (-4x^2)-40x-40=0 | | 3x+7-2x=15 | | u^2-10u+24/48-3u^2 | | x^2-2x-39=0 | | (5z^11)(-3z^6)(z^4)=y | | 1/2+4x-7=53 | | (5z^11)(-3z^6)(z^4)= | | 7x=4+30 | | (8x^2+y^2-6)-(6x^2+y^2-2)= | | (8x^2+y^2-6)-(6x^2+y^2-2)=b | | 6z=13-19 | | (8x^2+y^2-6)-(6x^2+y^2-2)=x | | (x^2)+8x=-12 | | -2(7x-3)+8=-14x+14 | | 10n^2+4n^3=0 | | 6y-12=2y-4 | | 6-5(-2+2)=8+(-2) | | X^2-5/x-3 | | -3x+5y=4 | | (x^2)-35=-2x | | P+C=97 | | 12/0.50 | | -x=9x+2 |